Discovery of HIV fusion inhibitors targeting gp41 using a comprehensive α-helix mimetic library - Whitby, Landon R. (2012)
[Image: see text] The evaluation of a comprehensive α-helix mimetic library for binding the gp41 NHR hydrophobic pocket recognizing an intramolecular CHR α-helix provided a detailed depiction of structural features required for binding and led to the discovery of small molecule inhibitors (K(i) 0.6–1.3 µM) that not only match or exceed the potency of those disclosed over the past decade, but that also exhibit effective activity in a cell–cell fusion assay (IC(50) 5–8 µM).